A new species of the pontoniine shrimp genus Eupontonia (Crustacea: Decapoda: Caridea: Palaemonidae) from the Ryukyu Islands, Japan - Komai, Tomoyuki; Minemizu, Ryo (Zootaxa, 2014)
A third species of the pontoniine shrimp genus Eupontonia Bruce, 1971, E. gracilipes n. sp., is described and illustrated on the basis of a single female specimen collected from shallow water of Ishigaki Island, southern Ryukyu Islands, Japan. The new species is readily distinguished from the two congeneric species, E. noctalbata Bruce, 1971 and E. oahu Bruce, 2010, by a number of morphological characters, including the presence of a distinct postrostral median ridge and of the postrostral median tooth on the carapace. It is considered to be a free-living species. The generic diagnosis of Eupontonia is slightly emended to accommodate the present new species. A key in aid of identification of species of Eupontonia is provided.